Teacher as a Creator of Child’s Aesthetic Space - Pawlak, Magdalena (Nauczyciel wczesnej edukacji: Rozwijanie kompetencji zawodowych, 2016)
Teacher as a creator of children’s visual aesthetic space has to consider his own abilities and child’s perceptive capabilities. Another important factor is child’s feedback which became a base for analysis of chosen examples of kindergartens and schools space arrangements. The article outlines the following teacher’s tasks: being respectful of child’s needs, caring about high aesthetic standards, limiting the amount of decorations as well as involving children in the creation process.